The extent use of the WACC by companies in Iceland - Lilja Björg Guðmundsdóttir 1977- (2017)
In this paper, the results of a quantitative research among CFOs in companies in Iceland on their usage of valuation techniques are presented. Chief Financial Officers (CFOs) in Icelandic companies were asked, in a questionnaire, whether they are using the Cost of Capital estimations to evaluate their operations. Other CFOs were also asked, in qualitative research, if they are using the Cost of capital estimations, and then if not then which methods are they using either instead or along with it. The Cost of Capital estimations refer to the calculations for the Weighted Average Cost of Capital (WACC). That is a financial calculation method for the WACC that gives CFOs clear picture to be able to evaluate their companies’ operation or a new project. To calculate the WACC the Capital Asset Pricing Model (CAPM) is used, which describes the relationship between expected return of assets and systematic risk (Investopedia, N/A). There are European (Brounen, De Jong & Koedijk, 2004), U.S. (Graham & Harvey, 2001) and Australian (Truong, 2008) researches that are all studying similar topic as in this research thesis. In the Australian research, there are results showing that the most popular techniques used for valuation of a business are the Net Present Value (NPV), the Internal Rate of Return (IRR) and the Payback period. The Weighted Average Cost of Capital (WACC) is most often used for discounting, with the assumption that the life of the project would be constant with same discount rate across departments. In this research thesis it is analysed whether companies in Icelandic do prefer to use the WACC as their valuation technique or if there are any other methods more used. The Australian research is a prefiguration of this research and the results are compared to the results of that research. The main results in this research thesis is that the WACC is used in 41% of the companies that participated in the research. CFOs are mainly using the Payback period method for evaluation in their companies, but also ...